309 Achieving Heavier Market Weights, with Similar Feed Efficiency, in Gilts Administered Improves. (21st September 2022) - Vonnahme, Kimberly A; Amodie, Debbie; Edler, Roy; Mellencamp, Marnie; Galina-Pantoja, Lucina
Abstract: Previous reports indicate that gilts administered Improvest will have an increased ADFI, ADG, and heavier market weights. Feeder type may influence growth performance and feed efficiency. Prior to the initiation of this study, pigs were placed into pens with two different feeder types at weaning (wet/dry shelf feeders and 4-hole dry feeders). Our objective was to determine grow-finish production parameters within a feeder type. Our null hypothesis was that Improvest would not impact ADFI, ADG, or feed efficiency. Pigs (63 days of age; d0 of the study) were weighed, and pens were randomized to treatment within a feeder type (20 pens/treatment; 27 gilts/pen). The first Improvest dose was administered on d7 and the second dose administered on d67. Weights were obtained at each dietary phase change, and prior to each marketing. The heaviest 8 gilts/pen were marketed 22 days post second dose (PSD), heaviest 8 gilts/pen at 37 days PSD, and all remaining gilts marketed at 50 days PSD. The phenotypes were similar between the 2 feeder types. Prior to the 2 nd dose of Improvest, ADFI, ADG, and weights were similar between Improvest-treated and control gilts. After the 2 nd dose, ADFI, ADG, and live weights were increased in Improvest gilts. Feed efficiency (G:F) was similar at all times between treatment groups. There was an increased (P ≤ 0.05) market weight and carcass weight for Improvest-treated gilts; however, this was driven by gilts marketed at 37- and 50-days PSD, as weights were similar for Improvest and control gilts 22 days PSD. Feed efficiency was similar with Improvest administration in gilts. To optimize the impacts of Improvest, marketing times should be considered when planning the Improvest administration schedule, as the weight advantages were not realized until after the first marketing cut.